"Like a wake-up call for humankind": Views, challenges, and coping strategies related to public health measures during the first COVID-19 lockdown in Thailand. - Bhensri Naemiratch; Mira Leonie Schneiders; Tassawan Poomchaichote; Supanat Ruangkajorn; Anne Osterrieder; Wirichada Pan-Ngum; Phaik Yeong Cheah (PLOS Global Public Health)
Following the first Thai COVID-19 case in January 2020, the Thai government introduced several non-pharmaceutical interventions (NPIs) in March 2020 (e.g., contact tracing, travel restrictions, closure of businesses, curfews, stay at home orders) to control COVID-19 transmissions. This study aimed to understand the views and experiences of a small number of Thai residents related to public health measures implemented during the first COVID-19 wave in Thailand. A total of 28 remote in-depth interviews with Thai residents (18-74 years old) were conducted between 8 May and 21 July 2020. Interviews were audio recorded, transcribed, and analysed using thematic analysis based on the Framework Method. Our results describe participants' views, challenges, and coping strategies relating to COVID-19 restrictions. Most participants expressed support for the introduction of strict public health measures, while some criticized lacking enforcement or rational of certain measures. Participants identified four major challenges, namely financial hardship; social isolation and loneliness; stigma and shaming; and fear of COVID-19 infection. Strategies adopted to address these challenges included practical coping strategies (e.g., reducing risks and fear of COVID-19 infection; mitigating financial, social, and mental health impacts), and embedded socio-cultural ways of coping (e.g., turning to religion; practicing acceptance; kindness, generosity and sharing ('Namjai'); 'making merit' ('Tham-bun')). The challenges identified from this study, in particular the role of stigma and discrimination, may be relevant to other infectious disease outbreaks beyond COVID-19. Findings from this study underscore the need for policies and interventions that mitigate the negative impacts of NPIs on the public, particularly on vulnerable groups, and highlight the importance of considering socio-cultural context to support community resilience in times of crisis. Our findings remain relevant in light of low COVID-19 vaccine availability and the potential need to implement further public health restrictions in Thailand and elsewhere against COVID-19 or future infectious disease threats.